ENT 530 Social Media Portfolio : Dodol Mereciks Warisan Melaka / Izham Hajar - Hajar, Izham (2019)
Dodol Mereciks Warisan Melaka was established on 30 September 2018. The business was manage by myself and under management, headed by General Manager and Marketing Manager, lzham Bin Hajar, Finance manager and Administration Manager, and Operational Manager, to perform organization's task.